The Impact of the Level of Bank Competition on Credit Risk in ASEAN-5 Countries - Natalena, Desi Putri; Viverita, Viverita (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2024)
This research aims to determine the effect of bank competition on credit risk in ASEAN-5 countries. The sample used for this research are banks in ASEAN-5 with a total of 21 banks with a research period from 2011 - 2022. In this research, a panel data regression method was used using the Two Step Generalized Method of Moments (GMM). This research found that banks with higher competition level can reduce their credit. The results support the competition-stability theory. Banks can implement strategies to increase their competitiveness, such as product and service innovation, to reduce credit risk. In addition, banking regulators can use the results of this research to encourage healthy competition in the banking sector to strengthen financial system stability.